Strengthening Vaccine Regulation: Insights from COVID-19 Vaccines, Best Practices, and Lessons for Future Public Health Emergencies - Razieh Ostad Ali Dehaghi; Alireza Khadem Broojerdi; Alaa Magdy; Marie Valentin; Juliati Dahlan; Obaidullah Malik; Richard H. Siggers; Edwin Nkansah; Hiiti B. Sillo (Vaccines, 2025)
Background: The COVID-19 pandemic necessitated immediate regulatory vaccine approvals to facilitate timely global access. The prevailing differences in economies and resources and the varying maturity of the regulatory systems worldwide resulted in different levels of capacity to ensure vaccine quality, safety, and efficacy. In addition to the Emergency Use Authorization or equivalent by some advanced regulatory agencies, the WHO issued Emergency Use Listings (EULs), among other tools, to streamline and expedite regulatory approvals globally. This study aimed to assess the regulatory strategies and best practices adopted during the COVID-19 vaccine approvals and gather lessons for future emergency preparedness. Methods: A mixed-method approach employing qualitative desk reviews and a cross-sectional study collected data from 194 national regulatory authorities (NRAs) across all WHO regions. Results: Three main approval processes were identified: procurement-driven, reliance-based, and independent evaluations. Wealthier countries with more mature regulatory systems were found to spend a longer time issuing approvals, primarily due to being the initial assessors of the vaccines’ quality, safety, and efficacy. Furthermore, various regulatory flexibilities and best practices centered around regulatory reliance, rolling reviews, fast-tracking reviews, and employing digital tools were identified. Notably, the WHO’s EULs were essential in facilitating the timely approval of vaccines globally, including in low- and middle-income countries. Conclusions: The findings suggest a significant turn in vaccine regulation theories and practice, emphasizing balancing speed with scientific validity. This necessitates the creation of thorough provisions for emergency preparedness, regulatory reliance, and administrative flexibility in regulatory practices worldwide.